Simplified mathematics of investment - Fajardo, Max B.,Jr (Quezon City, 2000)
Mathematics of Investment primarily deals with money transactions associated with interest and time. In any type of money transactions no less than two persons are involved - the debtor and the creditor; the buyer and the seller. This book is intended for the above definitions. The text is designed to provide a simplified course on the theories and applications of: Simple Interest and Simple Discount; Compound Interest, Simple Annuities; Amortization and Sinking Fund, Bonds, Depreciation, Capitalization and Perpetuities, Life Annuities and Life Insurance.
Keywords: Investment -- Mathematics